2011
DOI: 10.1590/s0074-02762011000700013
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary histories of expanded peptidase families in Schistosoma mansoni

Abstract: Schistosoma mansoni is one of the three main causative agents of human schistosomiasis, a major health problem with a vast socio-economic impact. Recent advances in the proteomic analysis of schistosomes have revealed that peptidases are the main virulence factors involved in the pathogenesis of this disease. In this context, evolutionary studies can be applied to identify peptidase families that have been expanded in genomes over time in response to different selection pressures. Using a phylogenomic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…The search for new drug targets based on evolutionary analyses using S. mansoni genomic/proteomic data has been performed (Silva et al, 2011, 2012). Such studies have improved the S. mansoni functional annotation, allowed for a deeper understanding of the genomic complexity and lineage-specific adaptations potentially related to the parasitic lifestyle, and pointed out several proteins as potential drug targets, including proteases.…”
Section: Introductionmentioning
confidence: 99%
“…The search for new drug targets based on evolutionary analyses using S. mansoni genomic/proteomic data has been performed (Silva et al, 2011, 2012). Such studies have improved the S. mansoni functional annotation, allowed for a deeper understanding of the genomic complexity and lineage-specific adaptations potentially related to the parasitic lifestyle, and pointed out several proteins as potential drug targets, including proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most significant protein expansions in S. mansoni we identified tetraspanins, fucosyltransferases, venom allergen-like proteins (SmVAL), tegumental-allergen-like proteins (SmTAL), leishmanolysins, and elastases, which were previously proposed as drug targets, once they can be related to morphological or physiological specificities of this parasite [5,20,61-65]. In these cases, the protein family membership ranged from 6 to 23 paralogs encoded in the parasite’s genome.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also revealed that these proteases can be employed by schistosomes to overcome or evade the host immune response [77,78]. Members of S. mansoni peptidase families such as leishmanolysins, cercarial elastases, and cathepsin D proteins were subjected to a detailed study in respect to their domain architectures, functional properties, and evolutionary relationships as described elsewhere [65]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, phylogenomics has unraveled the distinct evolutionary histories of three expanded endopeptidase families in S. mansoni [45]. This analysis included members of the metallopeptidase M8, serine peptidase S1, and aspartic peptidase A1 families, which were originated from successive events of gene duplication followed by divergence in the parasite lineage after its diversification from other metazoans.…”
Section: Evolutionary Genomics and Biodiversitymentioning
confidence: 99%
“…Leishmanolysins, which are members of the metallopeptidase M8 family, were analysed in detail corroborating the potential of these enzymes as future therapeutic targets [45]. …”
Section: Schistosoma Transcriptomicsmentioning
confidence: 99%